Social limits to growth - Hirsch, Fred. (Cambridge, Mass. : Harvard University Press, 1976)
This book suggests that the impasse on a number of key issues in the political economy of advanced nations is attributable in part to an outmoded perspective on the nature and therefore the promise of economic growth.
"A Twentieth Century Fund study."
Includes index.
Includes bibliographical references: p. 193-202
osa 07/11/18
Loans
Keywords: Economic development--Social aspects; Income distribution